2010
DOI: 10.1007/s11103-010-9624-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation explains most transcriptomic changes among maize plants of MON810 and comparable non-GM varieties subjected to two N-fertilization farming practices

Abstract: The introduction of genetically modified organisms (GMO) in many countries follows strict regulations to ensure that only safety-tested products are marketed. Over the last few years, targeted approaches have been complemented by profiling methods to assess possible unintended effects of transformation. Here we used a commercial (Affymertix) microarray platform (i.e. allowing assessing the expression of approximately 1/3 of the genes of maize) to evaluate transcriptional differences between commercial MON810 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 58 publications
5
40
0
2
Order By: Relevance
“…In real agricultural conditions, under two farming practices (conventional and low-nitrogen fertilization), Coll et al (2010a) found differential expression for only 0.14% of the analyzed sequences (approximately one-third of the maize genome). Analysis of the expression of a subset of sequences in a different MON810/non-GE pair indicated that varietal differences had the highest impact on gene expression patterns, followed by nitrogen availability, while the MON810 characteristic had the lowest impact.…”
Section: Maizementioning
confidence: 94%
“…In real agricultural conditions, under two farming practices (conventional and low-nitrogen fertilization), Coll et al (2010a) found differential expression for only 0.14% of the analyzed sequences (approximately one-third of the maize genome). Analysis of the expression of a subset of sequences in a different MON810/non-GE pair indicated that varietal differences had the highest impact on gene expression patterns, followed by nitrogen availability, while the MON810 characteristic had the lowest impact.…”
Section: Maizementioning
confidence: 94%
“…Transcriptomics, proteomics and metabolomics analysis showed small differential transcripts/proteins/metabolites between MON810 and non-GM samples (Coll et al 2008;Manetti et al 2006;Piccioni et al 2009); and the effects of varying environmental conditions were higher than those of the transgene (Barros et al 2010;Coll et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The differences between GM and non-GM maize (''unexpected effects'') may not be the same when different variety pairs are compared. Only a few previous works based on transcriptomics and metabolomics took into account different MON810 and near-isogenic varieties; and remarkably they showed that transcripts and metabolites mostly show altered concentrations in MON810 and non-GM samples in a variety specific manner (Coll et al 2008(Coll et al , 2010Levandi et al 2008). Although this approach has been recommended by several authors (Ruebelt et al 2006;Van Dijk et al 2009), a proteomics based research to cover this aspect is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of articles, Coll et al reported the comparative study of different MON810 varieties with their near-isogenic counterpart [42,43]. In the first study, after in vitro culturing of the maize plantlets under highly controlled experimental conditions (to avoid changes due to environmental factors), high-density Affymetrix microarray technology was used to analyze the gene expression [42].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…These results suggest that the genetic background of each variety has a great influence when assessing the substantial equivalence of GM crops. In a later study, a similar methodology was applied to assess the effect of different field environments and cultural conditions over MON810 maize varieties and their counterparts [43]. Microarray data revealed a deregulation of 0.07-0.2% of the maize transcriptome when growing the plants under low-nitrogen and control conditions.…”
Section: Transcriptomicsmentioning
confidence: 99%